Role of Nanoparticles in Enhancing Crop Tolerance to Abiotic Stress: A Comprehensive Review - El-Saadony, Mohamed T.; Saad, Ahmed M.; Soliman, Soliman M.; Salem, Heba M.; Desoky, El-Sayed M.; Babalghith, Ahmad O.; El-Tahan, Amira M.; Ibrahim, Omar M.; Ebrahim, Alia A. M.; Abd El-Mageed, Taia A.; Elrys, Ahmed S.; Elbadawi, Alaa A.; et al. (Frontiers in Plant Science, 2022)
Plants are subjected to a wide range of abiotic stresses, including heat, cold, drought, salinity, flooding, and heavy metals. Generally, abiotic stresses have adverse impacts on plant growth and development; thereby affecting agricultural productivity, causing food security problems, and resulting in economic losses. Novel technologies, such as nanotechnology, have been emerged to minimize the unfavorable impact of environmental stress on crop plants. The use of nanotechnology in modern agriculture can also help increase water use efficiency, prevent plant diseases, ensure food security, reduce environmental pollution, and enhance sustainability. In this regard, nanoparticles (NPs) can combat nutrient deficiencies, promote stress tolerance, and improve yield and quality of crops. This can be achieved by stimulating the activity of certain enzymes, increasing the contents (e.g. chlorophyll) and effciciency of photosynthesis, and controlling plant pathogens. The use of nanoscale agrochemicals, including nanopesticides, nanoherbicides, and nanofertilizers, has recently acquired increasing interest as potential plant-enhancing technologies. This review acknowledges the positive impacts of NPs in sustainable agriculture, and highlights their adverse effects on the environment, health and food chain. Here, the role and scope of NPs as a practical tool to enhance yield and mitigate the detrimental effects of of abiotic stresses in crops are described. the future prospective of nanomaterials in agriculture has also been discussed.